Basic neurochemistry : principles of molecular, cellular, and medical neurobiology - Siegel, George J.; Albers, R. Wayne (Robert Wayne); Price, D. L. (Donald Lowell); Brady, Scott T. (Academic Press, 2012)
Basic Neurochemistry: Principles of Molecular, Cellular, and Medical Neurobiology, the outstanding and comprehensive classic text on neurochemistry, is now newly updated and revised in its Eighth Edition. For more than forty years, this text has been the worldwide standard for information on the biochemistry of the nervous system, serving as a resource for postgraduate trainees and teachers in neurology, psychiatry, and basic neuroscience, as well as for medical, graduate, and postgraduate students and instructors in the neurosciences. The text has evolved, as intended, with the science. It is.